Randomized Phase II Study Comparing Prophylactic Cranial Irradiation Alone To Prophylactic Cranial Irradiation And Consolidative Extra-Cranial Irradiation For Extensive Disease Small Cell Lung Cancer (ED-SCLC): NRG Oncology RTOG 0937 - Gore, Elizabeth M (J Thorac Oncol, 2017)
INTRODUCTION: RTOG-0937 is a randomized phase-II trial evaluating 1-year OS with PCI or PCI plus consolidative radiation therapy (cRT) to intra-thoracic disease and extracranial metastases for ED-SCLC. METHODS: Patients with 1–4 extracranial metastases were eligible after CR or PR to chemotherapy. Randomization was to PCI or PCI+cRT to the thorax and metastases. Original stratification included PR vs CR after chemotherapy and 1 vs 2–4 metastases; age < 65 vs ≥ 65 was added after an observed imbalance. PCI was 25GY/10 fractions. cRT was 45GY/15 fractions. To detect an OS improvement from 30% to 45% with a 34% hazard reduction (HR=0·66) under a 0.1 type-1 error (1-sided) and 80% power, 154 patients were required. RESULTS: Ninety-seven patients were randomized between March, 2010 and February, 2015. Eleven patients were ineligible (nine PCI, two PCI+cRT), leaving 42 randomized to PCI and 44 to PCI+cRT. At planned interim analysis the study crossed the futility boundary for OS and was closed prior to meeting accrual target. Median follow-up was 9 months. One-year OS was not different between the groups: 60.1% [95% CI: 41.2–74.7%] for PCI and 50.8% [95% CI:34.0–65.3%] for PCI+cRT (p=0.21). Three and 12-month rates of progression were 53.3% and 79.6% for PCI, and 14.5% and 75% for PCI+cRT. Time to progression favored PCI+cRT, HR=0.53 (95% CI: 0.32–0.87, p=0.01). One-patient in each arm had Grade-4 therapy related toxicity and one had Grade-5 therapy related pneumonitis with PCI+cRT. CONCLUSIONS: OS exceeded predictions for both arms. Consolidative RT delayed progression but did not improve 1-year OS.